Knowns and Unknowns of Assaying Antibody-Dependent Cell-Mediated Cytotoxicity Against HIV-1 - Lewis, George K.; Ackerman, Margaret E.; Scarlatti, Gabriella; Moog, Christiane; Robert-Guroff, Marjorie; Kent, Stephen J.; Overbaugh, Julie; Reeves, R. Keith; Ferrari, Guido; Thyagarajan, Bargavi (Frontiers in Immunology, 2019)
It is now well accepted that Fc-mediated effector functions, including antibody-dependent cellular cytotoxicity (ADCC), can contribute to vaccine-elicited protection as well as post-infection control of HIV viremia. This picture was derived using a wide array of ADCC assays, no two of which are strictly comparable, and none of which is qualified at the clinical laboratory level. An earlier comparative study of assay protocols showed that while data from different ADCC assay formats were often correlated, they remained distinct in terms of target cells and the epitopes and antigen(s) available for recognition by antibodies, the effector cells, and the readout of cytotoxicity. This initial study warrants expanded analyses of the relationships among all current assay formats to determine where they detect overlapping activities and where they do not. Here we summarize knowns and unknowns of assaying ADCC against HIV-1.